Modelling nutrient transport and transformation by pool‐breeding amphibians in forested landscapes using a 21‐year dataset. (24th November 2014) - Capps, Krista A.; Berven, Keith A.; Tiegs, Scott D.
Summary Migrations of animals can transfer energy and nutrients through and among terrestrial and aquatic habitats. Pool‐breeding amphibians, such as the wood frog (Lithobates sylvaticus), make annual breeding migrations to ephemeral wetlands in forest habitats in the eastern and midwestern United States and Canada. To model the influence of wood frogs on nutrient transport and transformation through time, we coupled long‐term population monitoring data (1985–2005) from a wood frog population with estimates of the elemental composition of wood frog egg masses and emerging juveniles. Over the 21‐year study period, 8.8 kg carbon (C), 2.0 kg nitrogen (N) and 0.20 kg phosphorus (P) were transported from the terrestrial to the aquatic habitat and approximately 21 kg C, 5.5 kg N and 1.2 kg P were exported to the surrounding terrestrial habitat by wood frogs. During the study period, the average net flux of C, N and P was from aquatic to terrestrial habitats, but the magnitude and direction of the net flux was element dependent. Thus, the net flux of C, N and P did not always flow in the same direction. Predicting long‐term trends in nutrient and energy flux by organisms with biphasic life cycles should rely on long‐term population data to account for temporal variability. This is especially true for organisms that are sensitive to long‐term shifts in temperature and precipitation patterns, such as amphibians that breed in ephemeral pools.